2011
DOI: 10.1039/c0pp00232a
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the awareness and understanding of the ultraviolet index forecasts in the South West of England

Abstract: Despite large sun protection behaviour intervention campaigns there has not been a marked reduction in the incidence of skin cancer. This study explored the awareness and understanding of global solar UV index (UVI) information presented to the public in weather forecasts and whether individuals changed their sun exposure/protection behaviour as a result of receiving such information. A cross-sectional, face-to-face survey was undertaken in Devon and Cornwall in the South West of England between 20 August and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Nevertheless, at the moment, understanding of the UVI remains poor in many countries. 7,46,47 We have shown that with some knowledge of personal skin type, a simple calculation can provide the maximum allowable time outdoors before minimal erythema of the skin occurs. There are safety factors built into this approximation, including that exposure to full sunlight is unlikely for the full duration of the time outdoors, the calculation assumes exposure to a horizontal unshaded surface, and the mathematical approximation itself is conservative.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, at the moment, understanding of the UVI remains poor in many countries. 7,46,47 We have shown that with some knowledge of personal skin type, a simple calculation can provide the maximum allowable time outdoors before minimal erythema of the skin occurs. There are safety factors built into this approximation, including that exposure to full sunlight is unlikely for the full duration of the time outdoors, the calculation assumes exposure to a horizontal unshaded surface, and the mathematical approximation itself is conservative.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of participants (57%) believed that it would be good or very good if newspapers presented a daily report of the UVI 18 . Morris and associates 17 found that of 67% of UVIaware participants in Southwest England, 60% reported that UVI did not impact their behavior. Also in the UK, Diffey and colleagues 25 found that about one third of respondents reported that they had used the UVI at least once to plan their sun exposure.…”
Section: Relationship Of Uvi With Sun Exposure and Protective Behaviorsmentioning
confidence: 99%
“…A study found that only 27% of the Swedish participants had heard of the UVI; although, 41% of those believed that they became better informed about UVR because of the UVI 18 . In the UK, researchers found that 67% of participants had heard of the UVI 17 . However, of those, only 40% were able to correctly identify a "high" UVI value, and only 8% were able to recall the UVI value on that day.…”
Section: Awareness and Understanding Of The Uvimentioning
confidence: 99%
“…338 However, its use to guide behaviour in relation to exposure to the sun remains limited. 339 Furthermore, the specific guidance in relation to the UVI varies across different countries. For example, in Australia, photoprotection is recommended when the UV Index is ≥3.…”
Section: Personal Protection From Solar Uv Radiationmentioning
confidence: 99%